2005
DOI: 10.1007/s00464-004-2240-1
|View full text |Cite
|
Sign up to set email alerts
|

The Eindhoven laparoscopic cholecystectomy training course—improving operating room performance using virtual reality training: results from the first E.A.E.S. accredited virtual reality trainings curriculum

Abstract: The Eindhoven Virtual Reality laparoscopic cholecystectomy training course improves surgical skill in the operating room above the level of residents trained by a variety of other training methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 15 publications
1
71
0
2
Order By: Relevance
“…In practice, this is often established by measuring a logical difference in outcome between research populations with different levels of experience on a specific task of interest. Multiple studies have been conducted to validate different virtual reality systems as tools for training surgeons in endoscopic surgery skills [3,4,6,10,[13][14][15][16][17]. These studies demonstrated construct validity for these systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, this is often established by measuring a logical difference in outcome between research populations with different levels of experience on a specific task of interest. Multiple studies have been conducted to validate different virtual reality systems as tools for training surgeons in endoscopic surgery skills [3,4,6,10,[13][14][15][16][17]. These studies demonstrated construct validity for these systems.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of incorporating virtual reality training into the surgical curriculum has been suggested only recently and therefore validation testing for simulation concepts is a very recent development [3,4,6,10,[13][14][15][16][17].…”
mentioning
confidence: 99%
“…Although this implementation study was not designed to calculate costs, it is interesting to debate how high costs may be to minimize complications; however, this was beyond the scope of this study. Alternative options to monitoring learning curves have been described including workshops, bench or animal models, and virtual-reality programs [21][22][23][24][25][26][27]. Most of these methods are developed for training in basic skills of laparoscopy or as an introduction to a more advanced procedure, but most often not suitable to learn level 3 procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In gynecology, Larsen et al (26) demonstrated that training on the LapSim ® resulted in improved STS during a laparoscopic salpingectomy with respect to time and to a validated score. Moreover, both Xitact LS500 ® and LAP Mentor demonstrated a significantly positive impact on STS in the oR in nonrandomized comparative studies (27,28). Finally, beyond training to acquire STS, VR simulators have also demonstrated a positive impact as a warm-up tool for surgeons before doing a laparoscopic cholecystectomy (29).…”
Section: Transfer Of Technical Skillsmentioning
confidence: 99%